A Case Report of Tyzzer’s Disease in Two Kittens in Japan - Karmacharya, R; Chambers, J.K.; Kishimoto, T.E.; Uchida, K; Nakayama, H (Nepalese Veterinary Journal, 2023)
Available within the full article